Collective fodder cultivation an idea worth emulation from Idukki, Kerala - V, Sreeram; Gupta, Jancy (Indian Farming, 2018)
The efforts of these women became a success mainly because of their cooperation and among them to work together to meet their common objective. i.e. to meet the fodder demand without any conflicts. Also the timely support which they got from the Dairy Development Department became a crucial factor in their success. Such initiatives are of worth replication in other parts of the state too, as fodder scarcity is the most serious challenge that the dairy farmers face today. The Dairy Development Department, the nodal agency for fodder development activities on its part can promote such Self-help Groups/ Joint Liability Groups/Food Product Orders who are willing to take up fodder cultivation.